From integration to modelling. On a neglected function of the methodology of humanities - Boruszewski, Jarosław; Nowak-Posadzy, Krzysztof (Wydawnictwo Naukowe UAM, 2019)
The aim of this paper is two-fold: to engage the contemporary discussion about the nature of relations between different scientific disciplines, as well as to disentangle the concept of integration of sciences from superstructures of rival proposals. The authors start with a critical analysis of the Polish contribution to the discussion about the nature of integration of sciences from the second half of the XXth century. Such a step is followed by elaborating a refined account of integration and by disentangling the concept of integration from superstructures of rival proposals – unification and interdisciplinarity. On the grounds of such a refined account the authors deliver a reconstruction of a successful scientific integration. In doing this they introduce the idea of connective knowledge as generated by the methodology of humanities. After reconstructing the successful integration trial, in the concluding remarks their account of integration is specified and summarized.
Keywords: methodology of humanities; integration; unification; interdisciplinarity; model of primitive magic syncretism; Poznań Methodological School